Role of the Eye in Transmitting Human Coronavirus: What We Know and What We Do Not Know - Sun, Chuan-bin; Wang, Yue-ye; Liu, Geng-hao; Liu, Zhe (Frontiers in Public Health, 2020)
The outbreak of current 2019 novel coronavirus (2019-nCoV, now named as SARS-CoV-2) infection has become a world-wide health threat. Currently, more information is needed for further understanding the transmission, clinical characteristics, and infection control procedures of 2019-nCoV. Recently, the role of the eye in transmitting 2019-nCoV has been intensively discussed. Previous investigations about other highly infectious human CoVs, that is, severe acute respiratory syndrome coronavirus (SARS-CoV) and the Middle East respiratory syndrome coronavirus (MERS-CoV), may provide useful information. In this review, we describe the genomics and morphology of human CoVs, the epidemiology, systemic and ophthalmic manifestations, mechanisms of human CoVs infection, and infection control procedures. The role of the eye in the transmission of 2019-nCoV is discussed in detail. Although the conjunctiva is directly exposed to extraocular pathogens, and the mucosa of ocular surface and upper respiratory tract is connected by nasolacrimal duct and share same entry receptors for some respiratory viruses. The eye is rarely involved in human CoVs infection, conjunctivitis is quite rare in patients with 2019-nCoV infection, and CoV RNA positive rate by RT-PCR test in tears and conjunctival secretions from patients with 2019-nCoV and SARS-CoV infection is also extremely low, which implicates that the eye is neither a preferred organ of human CoVs infection, nor is a preferred gateway of entry for human CoVs to infect respiratory tract. However, pathogens exposed to the ocular surface might be transported to nasal and nasopharyngeal mucosa by constant tear rinsing through lacrimal duct system, and then cause respiratory tract infection. Considering close doctor-patient contact is quite common in ophthalmic practice which are apt to transmit human CoVs by droplets and fomites, strict hand hygiene and proper personal protection are highly recommended for health care workers to avoid hospital-related viral transmission during ophthalmic practice.